Percutaneous Transhepatic and Transsplenic Portal Vein Access: Embolization of the Puncture Tract Using Amplatzer Vascular Plugs - Dollinger, M.; Goessmann, H.; Mueller-Wille, R.; Wohlgemuth, W. A.; Stroszczynski, C.; Heiss, P. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2014)
Purpose: To report on first results of the embolization of transhepatic and transsplenic puncture tracts using an Amplatzer Vascular Plug (AVP) after percutaneous portal vein intervention.Materials and Methods: Embolization of transhepatic and transsplenic puncture tracts with AVP was attempted in 5 patients (3 females; age range: 3 – 71 years). Portal vein access was gained by a transhepatic (n = 4) or transsplenic (n = 1) approach, and stenosis (n = 2) or thrombosis (n = 3) of the portal vein was successfully treated by percutaneous stenting or thrombus aspiration and thrombolysis using 6 to 10 French sheaths. Due to the relatively large bore and/or short transparenchymal puncture tracts, it was considered favorable to use AVPs as an embolic agent. The medical records, the radiological reports and images of these 5 patients were retrospectively evaluated.Result: In three cases one AVP II (diameter, 4 mm), in one case one AVP IV (diameter, 4 mm) and in one case two AVPs II (diameter, 8 and 6 mm) were used for embolization of the puncture tract. In all five cases embolization was technically successful. There was no bleeding from the puncture tract. During a median follow-up of 14 months (range, 21 days to 21 months), one patient developed a focal liver abscess adjacent to the AVP which was successfully treated by antimicrobial and drainage therapy. There were no further embolization-related complications.Conclusion: AVPs are suited to embolize large bore and/or short transhepatic and transsplenic puncture tracts effectively, safely, and precisely. Caution is required in patients with an increased risk for infectious complications.Key Points:• Embolization of transhepatic and transsplenic puncture tracts with AVPs is feasible• Large and/or short puncture tracts can be effectively embolized with AVPs• The risk of infectious complications has to be consideredCitation Format:• Dollinger M, Goessmann H, Mueller-Wille R et al. Percutaneous Transhepatic and Transsplenic Portal Vein Access: Embolization of the Puncture Tract Using Amplatzer Vascular Plugs. Fortschr Röntgenstr 2014; 186: 142 – 150
Keywords: percutaneous transhepatic and transsplenic portal vein access; puncture tract embolization; Amplatzer Vascular Plug